Properties and growth of large single crystals of one-dimensional organic lead iodine perovskite. Issue 42 (13th October 2020) - Wang, Yiming; Liu, Yanliang; Wu, Yizhang; Jiang, Junjie; Liu, Chunlin; Liu, Wenlong; Gao, Kaige; Cai, Hongling; Wu, X. S.
Abstract : Here, we demonstrate for the first time the growth of 2 mm × 4 mm × 8 mm sized single crystal one dimensional organic lead iodine perovskite – DMAPbI3 ((CH3 )2 NH2 PbI3 ). Abstract : In general, it is hard to grow large single crystals with a one-dimensional chain structure due to the preferred growth direction and chain breakage. Most reported one-dimensional lead iodine chain single crystals can grow long, but they are difficult to grow thick. Here, we demonstrate for the first time the growth of 2 mm × 4 mm × 8 mm sized single crystal one dimensional organic lead iodine perovskite – DMAPbI3 ((CH3 )2 NH2 PbI3 ). Benzylamine addition to the solution may help to dissolve crystals with high defect concentrations so that the crystal can grow larger. Through the measurement on the large single crystal, we found that DMAPbI3 is ferroelectric below 260 K, and the dielectric constant of DMAPbI3 at various frequencies at room temperature is as high as more than 100. Blue photoluminescence centered at 2.6 eV was reported. The ferroelectricity of DMAPbI3 may be used to design more stable and efficient organometal halide perovskite solar cells and photoelectric devices.